On the nature of thermal equilibrium point defects in Si: Are the thermal equilibrium point defects in Si crystals Frenkel pairs or Schottky defects?. (27th March 2017) - Suezawa, Masashi; Iijima, Yoshiaki; Yonenaga, Ichiro
Abstract: Thermal equilibrium point defects (TEPD) are generated as Frenkel pairs or Schottky defects. It is still controversial whether the TEPD in Si are Frenkel or Schottky, which is recalled with the recent experimental finding of their formation energies. After reviews of the Frenkel pair and Schottky defects models, the latter was concluded to be the case since their formation energies determined experimentally are different from each other. This result was applied to calculate the critical ratio of the growth velocity/temperature gradient of the Voronkov model on the grown-in point defects in Si and obtained a different result.